أثر منطلقات تفعيل وتقصيد الوقف العلمي في التّنمية الاجتماعية والاقتصادية - موفق, نبيل (جامعة الوادي university of eloued, 2022)
يناقش البحث موضوع الوقف العلمي من حيث إسهامه في قيام نهضة اقتصادية وتنمية اجتماعية، ومحاولة تجلية المرتكزات المقاصدية التي يقوم عليها ذلك الإسهام، باعتباره مجموع الآليات والسّبل والطّرق والوسائل والمرتكزات والتّدابير التي يمكن اقتراحها أو استثمارها من أجل نشر ثقافة الوقف العلمي من النّاحية النّظريّة ومن النّاحية التّطبيقيّة أيضاً، سواءً كانت هذه الوسائل والآليات دينية شرعية، أو سياسية أو اقتصاديّة، أو اجتماعيّة، فردية كانت أو جماعية، فكلّ ما يمكن أن يسهم في نشاط العملية الوقفية في مجال العلم والتّعلّم فهو ما نقصده بالمنطلقات والسّبل والوسائل، وكان من نتائج البحث ضرورة الاهتداء بالاجتهاد المقاصدي والمصلحي في توجيه المحسنين الواقفين وفي تسيير أموال الوقف العلمي وفي تطبيق مناهجه باعتبار المنطلقات المقاصدية والنتائج المآلية، والمصالح المقصديّة والغايات التّنمويّة، والخطط الاستثمارية، والمناهج الاقتصادية مع وضوح الرّؤية لإصابة الهدف المنشود. Abstract: The research discusses the issue of the scientific endowment in terms of its contribution to the establishment of an economic renaissance and social development, and an attempt to clarify the intentional foundations upon which that contribution is based, as it is the sum of the mechanisms, ways, ways, means, foundations and measures that can be proposed or invested in order to spread the culture of the scientific endowment from the theoretical point of view and from the The practical aspect also, whether these means and mechanisms are legitimate religious, political, economic, social, individual or collective, everything that can contribute to the activity of the endowment process in the field of science and learning is what we mean by premises, ways and means, and one of the results of the research was a necessity To be guided by intentional and interest-based diligence in guiding endowed benefactors and in managing the funds of the scientific endowment and in applying its methods, considering the intentional premises and financial results, intentional interests and development goals, investment plans, and economic approaches with a clear vision of hitting the desired goal
مقال
Keywords: الوقف، ; العلمي، ; المنطلقات، ; التقصيد، ; التنمية، ; الاقتصادية، ; الاجتماعية.